If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(8x+9)=-3(16x+18)
We move all terms to the left:
-6(8x+9)-(-3(16x+18))=0
We multiply parentheses
-48x-(-3(16x+18))-54=0
We calculate terms in parentheses: -(-3(16x+18)), so:We get rid of parentheses
-3(16x+18)
We multiply parentheses
-48x-54
Back to the equation:
-(-48x-54)
-48x+48x+54-54=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| 0.10(y-7)+0.02y=0.20y-0.2 | | j+9=34 | | 32+m=20 | | 90+12x+7-1=180 | | 3/7=6/c | | 32-x+36=52 | | 2x-0.5x=17.5 | | y/3−2=2 | | 7x=9=1/4 | | 2−0.5n=3n+16 | | y/3− 2=2 | | 6d-2/11=2d−13/2 | | 2r−6=10 | | 16a+3a+36=64a+3a | | w+4/7=3 | | 2(x+5)-2=43-3x | | 10x+20/9=5 | | 12x-4=26 | | 7.3y−5.18=−51.9,y= | | 5x-3(x+1)=19 | | 2d−7=9 | | 3=u/4-1 | | 3x+225=9+15x | | 9(a-1)=5a-33 | | 6w-9=9(w-3) | | 5m+9=18-11m | | 5(t+3)=4t | | 2x+3/6-x+1/6=x+2/3-1 | | x+x+104+104+(x+18)+(x+18)=720 | | 6(x+2)+2x=-28 | | 14+2+4g-3)=40 | | -7(2x-10)=10 |